Light design in children's play environment - Belova Marina V. (Архитектон)
The article offers a review of domestic and foreign experiences in lighting design of children's playgrounds. The need to study this topic is due to the lack of clear differentiation of lighting equipment for children's play environments. The analysis includes the possibilities and prospects for the participation of light in children's play activities. Lighting design is considered in terms of its features, location and lighting scenarios. Based on a broad analysis of design experiences, a typology of lighting scenarios in a children's play environment is proposed, and examples of their implementation and characteristic features are presented. The typology will allow design proposals to be differentiated and the advantages of individual types to be used for high-quality lighting design for children's play environments.